Analgesic and Anti-allodynic Effects of Two Flavonoids in Partial Sciatic Nerve Ligation in Rat Model - Rana, A.C.; Gulliya, Bhawna; Rana, Swati (Indian Journal of Pharmaceutical Education and Research, 2019)
Background: Flavonoids, also called as bioflavonoids, are secondary metabolites of plants. Flavonoids, curcumin and hesperidin, possess various pharmacological activities such as analgesic, anti-ulcer, anti-parkinson, anti-cancer, spasmolytic, anti-bacterial, anti-depressant, anti-hypertensive, anti-arthritic and anti-inflammatory. Aim: The current study investigated the analgesic and anti-allodynic effects of flavonoids (curcumin and hesperidin) and compared their effects with pregabalin against experimentally induced neuropathic pain in Swiss albino rats. Methods: Behavioral parameters were investigated in partial sciatic nerve ligation rat model. Surgery was performed by exposing and ligating the right sciatic nerve. Heat hyperalgesic and cold allodynic tests were assessed using Eddy’s hot plate and submerging rat’s right hind paw in ice cold water (4 ± 1°C), respectively on days 4,7,10,13,16,19 and 22. Surgery was considered as day 1. Flavonoids and pregabalin (10mg/kg, p.o.) were administered for fifteen days. Results: Partial sciatic nerve ligation of right sciatic nerve significantly induced thermal hyperalgesia and cold allodynia. Administration of hesperidin (100mg/kg, p.o.) and curcumin (100mg/ kg, p.o.) showed significant increase in paw withdrawal latency in both the behavioral tests. Results of behavioral tests have shown curcumin to be a little more effective than hesperidin in attenuating the neuropathic pain. Conclusion: It can be concluded that both hesperidin and curcumin attenuate the neuropathic pain induced by partial sciatic nerve ligation in rats. However, curcumin showed more significant results than hesperidin.
Keywords: Flavonoids; Neuropathic pain; Analgesic; Anti-allodynic; Curcumin; Hesperidin; Partial Sciatic Nerve Ligation (PSNL); Hyperalgesic